2014
DOI: 10.1186/1750-9378-9-24
|View full text |Cite
|
Sign up to set email alerts
|

MDM2 polymorphism associated with the development of cervical lesions in women infected with Human papillomavirus and using of oral contraceptives

Abstract: BackgroundThe MDM2 gene is the major negative regulator of p53, a tumor suppressor protein. Single nucleotide polymorphism in promoter region of MDM2 gene leads to increased expression resulting in higher levels of MDM2 protein. This event increases the attenuation of the p53 pathway. Polymorphisms in this gene can interfere in the regulation of cellular proliferation. We evaluated whether MDM2 SNP309 (rs2278744) associated or not with the use of oral contraceptive can heighten susceptibility to development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…When patients were stratified by HPV samples, we observed an association between HPV positivity, the use of contraceptives, and the number of sexual partners. The results of this study corroborate previous findings from other studies that have shown a link between the use of contraceptives and HR HPV infection (Finan et al, 2002;Au, 2004;Chagas et al, 2013;Amaral et al, 2014). Therefore, our results suggest that behavioral factors might have an impact on the status of cervical cytology in our study population.…”
Section: Discussionsupporting
confidence: 92%
“…When patients were stratified by HPV samples, we observed an association between HPV positivity, the use of contraceptives, and the number of sexual partners. The results of this study corroborate previous findings from other studies that have shown a link between the use of contraceptives and HR HPV infection (Finan et al, 2002;Au, 2004;Chagas et al, 2013;Amaral et al, 2014). Therefore, our results suggest that behavioral factors might have an impact on the status of cervical cytology in our study population.…”
Section: Discussionsupporting
confidence: 92%
“…In 2012, according to World Health Organization, cervical cancer was one of the most prevalent cancer types in the world. To detect and diagnose cancer, there are several biomarkers; [20][21][22][23] for example, the Ki-67 protein is expressed in all phases of the cell division cycle, but its expression level is strongly downregulated in the resting G0 phase. This characteristic makes the Ki-67 protein an excellent biomarker for cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…34 The oral contraceptives alone have no effect on the progression or development of cervical lesions, but they can act in synergy, increasing the susceptibility to develop highdegree lesions in women infected with HPV. 35 Also, they can result in higher frequency of unprotected sexual intercourse, putting the women at risk of acquiring other STDs. 36 As regards the epithelium represented in the sample, it was possible to observe that women that had metaplastic epithelium had 1.3 times more chances to develop cellular changes in the cervix.…”
Section: Resultsmentioning
confidence: 99%